SEXUAL HARASSMENT, WORKPLACE AUTHORITY AND THE PARADOX OF POWER - Nyemeche Abraham , Chukwu (PT. Antis International Publisher, 2025)
Objective: This study investigates the paradox of power in workplace sexual harassment, focusing on how authority and power dynamics contribute to harassment incidents and perpetuate toxic organizational environments. Method: Utilizing a mixed-methods approach, the research combines quantitative surveys and qualitative interviews with employees across various industries to explore the relationship between authority, power imbalances, and harassment occurrences. Results: The findings reveal that power imbalances significantly facilitate harassment by enabling individuals in positions of authority to exploit their power without accountability. Organizational culture, inadequate reporting mechanisms, and fear of retaliation are identified as critical factors that sustain this paradox. Novelty: This study uniquely highlights the contradiction between the intended role of authority—to ensure structure and productivity—and its misuse as a tool for harassment. By emphasizing the need for ethical leadership and accountability, the research provides new insights into dismantling power dynamics that perpetuate workplace harassment. Recommendations include comprehensive organizational reforms, transparent reporting systems, and leadership training to promote ethical authority use, fostering safer and more equitable work environments.